Endometriosis and menopause—management strategies based on clinical scenarios - Ivika Jakson; Angelica Lindén Hirschberg; Sebastian B. Gidlöf (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Endometriosis is largely considered a premenopausal disease with symptoms often improving during menopausal transition. However, 2%–4% of postmenopausal women are affected by endometriosis symptoms. At the same time, many peri‐ and postmenopausal women experience menopausal symptoms and inquire about treatment. Because of the estrogen‐dependent nature of endometriosis, treatment with menopausal hormone therapy requires careful assessment of the patient but should nevertheless be considered. Recurrence of endometriosis symptoms and risk for malignant transformation are potential risks to weigh when prescribing menopausal hormonal therapy. Choice of treatment should be guided by the presence and severity of current endometriosis symptoms, nature of menopausal symptoms, risk assessment of potential contraindications for treatment in patient history, and preferences of the woman after an informative discussion. Recurrence of endometriosis symptoms in a postmenopausal patient should always prompt rigorous evaluation, both in the presence and absence of hormonal treatment. Many recommendations on the topic are based on expert opinion and new studies are urgently needed to obtain evidence for optimal patient care.